Religion and China’s Moral and Ethical Crisis - Doyle, G. Wright (Journal of Research for Christianity in China (JRCC), 2025)
China’s ethical and moral crisis seems to grow more serious every day. It extends from individuals tothe family, workplace, and all of society. Any religion that would hope to make a contribution to thiscrisis must offer three things: 1. Inner peace and moral transformation for individuals；2. Clear, authoritative teachings and the inner dynamic to transform families and all elements of society；3. Arelationship with God.This article proposes that Christianity fulfills all these requirements. It is alsofully rooted inChinese society, compatible with globalization, and a capable of motivating people tocare for the environment.